Optimal placement of multi-type FACTS devices to enhance total transfer capability using improved evolutionary programming - Weerakorn Ongsakul (2018)
An Improved Evolutionary Programming (IEP) is proposed to determine the optimal placement of multi-type Flexible AC Transmission Systems (FACTS) devices for maximising Total Transfer Capability (TTC) of power transactions. IEP simultaneously searches for types, locations, and parameters of FACTS devices, real power generations in source area, real power loads in sink area, and generation bus voltages to evaluate the feasible TTC value within power system constraints and FACTS devices operating limits. Test results on the modified IEEE 30- and 118-bus systems indicate that optimally placed optimal power flow (OPF) with FACTS by IEP could enhance TTC value far more than OPF without FACTS. Copyright © 2009, Inderscience Publishers.